Ultrastructure of rat lung following inhalation of ricin aerosol - BROWN, R. F. R. (Blackwell Publishing, 1997)
Ricin is one of a group of structurally related plant lectins and is extracted from the seeds of the Castor Oil plant, Ricinus communis. Groups of rats were exposed to ricin aerosol by inhalation, total LCt(1) = 11.21 mg.min.m(−3) (an approximate LCt(30) exposure) and examined, using transmission electron microscopy, at intervals up to 48 h after exposure. The first signs of change in ultrastructure were seen at between 6 and 12 h post exposure in alveolar macrophages and took the form of apoptotic changes primarily in the nucleus. These included heterochromatin condensation at the nuclear periphery and crenulation of the nuclear membrane. There then followed a sequence of changes in the cells of the alveolar wall and blood/air barrier culminating in intra-alveolar oedema at 12 and 15 h after exposure. Damage was first observed in the capillary endothelium and type I epithelial cell changes were evident from 12 h post exposure onward. These changes appeared to be necrotic rather than apoptotic in nature and suggest that mechanisms other than a direct effect of ricin may be involved. Associated with these changes were mixed inflammatory cell infiltrates in the interstitium, isolated type II pneumocyte necrosis and evidence of microvascular microthrombosis. By 48 h after exposure, the intra-alveolar oedema appeared less marked with prominent hyperplasia of type II pneumocytes. The identification that apoptosis of alveolar macrophages plays a significant part in the mechanism of toxicity following exposure to ricin raises the possibility of developing new therapeutic strategies against poisoning by ricin.